2015
DOI: 10.1177/1541931215591246
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Agent Transparency on Human Interaction with an Autonomous Robotic Agent

Abstract: We use the Situation awareness-based Agent Transparency model as a framework to design a user interface to support agent transparency. Participants were instructed to supervise an autonomous robotic agent as it traversed simulated urban environments. During this task, participants were exposed to one of three levels of information used to support agent transparency in the interface display. Our findings suggest that providing agent transparency information allows operators to properly calibrate trust without e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…The first theme we found was that transparency was associated with mixed findings. Indeed, studies find that higher transparency is related to increases in performance (e.g., Mercado et al, 2016), trust (Boyce et al, 2015), and perceived understanding of the autonomous agent (Harbers et al, 2011). Additionally, increasing agent transparency was associated with lower perceptions of time pressure and frustration (Wright et al, 2016).…”
Section: Independent Variablesmentioning
confidence: 99%
“…The first theme we found was that transparency was associated with mixed findings. Indeed, studies find that higher transparency is related to increases in performance (e.g., Mercado et al, 2016), trust (Boyce et al, 2015), and perceived understanding of the autonomous agent (Harbers et al, 2011). Additionally, increasing agent transparency was associated with lower perceptions of time pressure and frustration (Wright et al, 2016).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Of great interest to the HMT community was the reduction of workload found in the Benevolent condition. Findings from studies by Selkowitz et al (2015) and Mercado et al (2016) revealed that added transparency information did not mitigate workload. Transparency in previous work was provided within a SA model (see Barnes et al, 2017, for review) where visual displays were used to provide transparency into the system’s current state (Level 1), environmental constraints and logic (Level 2), and finally its projected state (Level 3).…”
Section: Discussionmentioning
confidence: 96%
“…Transparency is the intentional design of a system to communicate its capabilities and current state (Barnes et al, 2017; Lyons, 2013; Selkowitz, Lakhmani, Chen, & Boyce, 2015). It can be used to finely tune a human operator’s perception of the AT’s ability, intent, and situational constraints (Lyons, 2013).…”
Section: Supporting Affect Management With Transparencymentioning
confidence: 99%
“…Other transparency definitions, across domains, describe transparency as the communication of information regarding the machine’s abilities (Mercado et al, 2016) and capabilities (Wohleber, Stowers, Chen, & Barnes, 2017). Transparency has been described as a process (Nedbal, Auinger, & Hochmeier, 2013), method (Lyons, Sadler, et al, 2017; Selkowitz, Lakhmani, Larios, & Chen, 2016), mechanism (Lyons, 2013; Theodorou, Wortham, & Bryson, 2017), property (Selkowitz, Lakhmani, Chen, & Boyce, 2015), or emergent characteristic (Ososky, Sanders, Jentsch, Hancock, & Chen, 2014) that provides information or explanations (Kim & Hinds, 2006) to a human operator to develop accurate mental models of the system. The type of information provided, known as information transparency (Bruni, Marquez, Brzezinski, Nehme, & Boussemart, 2007), includes what (Mark & Kobsa, 2005) the human operator or machine is doing (Lyons, 2013) and why a particular task is being conducted (Sanders, Wixon, Schafer, Chen, & Hancock, 2014).…”
Section: Introductionmentioning
confidence: 99%